Binaural masking of amplitude modulation - Kordus, M.; Sęk, A.; Kociński, J. (Archives of Acoustics, 2005)
A new concept concerned with the transformation of acoustic stimuli in the auditory system postulates the existence of a form of spectral analysis applied to the amplitude changes of the stimuli. It is assumed that this analysis takes place in the so-called modulation filters, i.e. bandpass linear filters tuned to different rates of the amplitude changes. The most striking argument supporting this idea is an effect of masking in the amplitude modulation domain whose nature can be easily explained basing on this concept. As the modulation filters are situated on the higher levels of the auditory system, it is also assumed that this form of masking is entirely a central process. However, most of the studies concerned with masking in the modulation domain used monaural listening only. Therefore, the main purpose of the presented here experiments was to investigate whether this type of masking is entirely a central process. Using a Three-Alternative Forced-Choice (3AFC) procedure the binaural and monaural masked thresholds of amplitude modulation were determined. A sinusoidal carrier at a frequency of 4 kHz was amplitude modulated by a specially designed band of noise characterized by a very low value of the crest factor, which was used as a masking signals. Different bandwidths of the modulating masking signals were used as well as different center frequencies to investigate whether the masking patterns in the modulation domain depend on the masker bandwidth and its center frequency. The modulating target (masked) signal was a pure tone at a frequency range from 2 to 256 Hz. Both modulating signals were applied to the same sinusoidal carrier signal. The most effective masking was noticed when the rate of the sinusoidal modulation was close to the center frequency of the masking signal or when it was in its spectral range and decreased outside of this range. The character of this dependence confirms the existence of some form of a frequency selectivity in the modulation rate domain similarly to the audible frequency domain. The thresholds for monaural and binaural listening were very close to each other. This implies that masking in the modulation domain is a central process.